POLICIES AND SCENARIOS TO PREVENT THE USE OF NUCLEAR WEAPONS BETWEEN UNITED STATES AND CHINA IN THE SOUTH CHINA SEA - Winuhoro Hanumbhawono; Penny Radjendra; Suharto Ladjide (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
The issue of the South China Sea (SCS) dispute between the United States (U.S.) and China, which has not abated, has caused concern for countries in the region to escalate and lead to war from both sides. The thing that becomes the biggest threat when there is a nuclear war between the U.S. and China where will have an impact on several countries, one of them is Indonesia. This study tries to provide an overview of how to determine Indonesia's strategic policy from the hypothesis of existing policy options based on possible scenarios by formulating a strategic thinking framework to prevent the use of nuclear weapons as a result of the U.S.-China dispute in the SCS, using Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP) methods to determine the right policy strategy. The results of AHP and ANP methods show the same results, where ASEAN-SEANWFZ (The Association of Southeast Asian Nations-Southeast Asia Nuclear Weapons Free Zone) Multilateral Diplomacy is the Policy Choice that gets the biggest priority, and Peaceful Solutions become the Scenario that gets the highest priority.